Adolescence and vulnerability to sexually transmitted diseases: a documented research - Beserra, Eveline P.; Alves, Maria Dalva S.; Barroso, Maria Grasiela T. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: since a very early stage of life, adolescents should be given orientation on how to prevent STD. The use of an open dialog may allow them to express themselves and enlighten their doubts concerning this subject matter. Objective: build a documental research about the adolescents’ vulnerability towards STD/Aids from 1988 to 2006. Methods: it is a documental research developed as an activity of the Research Methodology II class of the Federal University of Ceará (UFC). The data was collected from books and published articles which focus on adolescence and sexuality. Analysis of the contents was used as a data basis. Then the results were categorized like the following: Adolescence; sexual life style and vulnerabili ties to STD; Safe sex and Sexual orientation. Results: the role of the nurse must be effective on building strategies which reach adolescents’ needs, focusing on details of their own life style. It is important to consider the adolescents behavior as they search for adventure and satisfaction most of the times concerned to strong feelings such as desire and passion. Conclusion: the school plays an important role as they give information about sexua lity as well as sexually transmitted diseases to minimize the risk factors through orientations which are appropriate to their reality as well as to per suade them to become more mature citizens.